The Effects of Leverage, Firm Size, and Market Value on Financial Performance in Food and Beverage Manufacturing Firms - Estiasih, Soffia Pudji; Suhardiyah, Martha; Suharyanto, Suharyanto; Putra, Andhika Cahyono; Widhayani, Puri Setioningtyas (Universitas Brawijaya, Indonesia, 2024)
Financial performance is an important phenomenon for measuring organizational success. This research aims to determine and analyze the influence of leverage, company size, and market value on financial performance. The research methods used are explanatory; the population used is food and beverage Manufacturing companies in the Food and Beverage sector listed on the Indonesia Stock Exchange for the 2017-2019 period are used to determine the number of samples in this study. From 31 December 2017 to 31 December 2019. The sampling technique used is a purposive sampling method and there are 12 companies published audited financial reports and reported them completely and consistently using the purposive sampling technique with criteria. The Source of data used is secondary data with a time series type of data. The hypothesis is tested using Partial Least Square (PLS) analysis with Smart PLS 3.0 software. The results show that Leverage has a significant effect on Financial Performance. At the same time, Firm Size had no significant effects on Financial Performance and Market Value had no significant effects on Financial Performance. This research implies that food and beverage companies need to develop financial strategies to improve their financial performance by increasing their leverage.